2013
DOI: 10.3201/eid1911.121843
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Phone–based Syndromic Surveillance System, Papua New Guinea

Abstract: The health care system in Papua New Guinea is fragile, and surveillance systems infrequently meet international standards. To strengthen outbreak identification, health authorities piloted a mobile phone–based syndromic surveillance system and used established frameworks to evaluate whether the system was meeting objectives. Stakeholder experience was investigated by using standardized questionnaires and focus groups. Nine sites reported data that included 7 outbreaks and 92 cases of acute watery diarrhea. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 18 publications
1
31
0
Order By: Relevance
“…Other mobile technologies including smartphone applications, patient monitoring devices, Personal Digital Assistants (PDAs), as well as laptops and tablets PCs connected with network service were piloted and implemented in various African countries [33]. Countries and development partners are eager to apply the mobile technology to capture real-time field data for surveillance and case management at the community level health care system [30,[34][35][36][37]. However, notable issues were documented including technical, financial, infrastructural challenges, data security and medical supports during the design and implementation process of mHealth surveillance in sub-Saharan Africa countries [33].…”
Section: Discussionmentioning
confidence: 99%
“…Other mobile technologies including smartphone applications, patient monitoring devices, Personal Digital Assistants (PDAs), as well as laptops and tablets PCs connected with network service were piloted and implemented in various African countries [33]. Countries and development partners are eager to apply the mobile technology to capture real-time field data for surveillance and case management at the community level health care system [30,[34][35][36][37]. However, notable issues were documented including technical, financial, infrastructural challenges, data security and medical supports during the design and implementation process of mHealth surveillance in sub-Saharan Africa countries [33].…”
Section: Discussionmentioning
confidence: 99%
“…Although mobile phones have been used during surveillance in several settings (e.g. after the 2008 Sichuan earthquake in China), 27,28 the use of highly automated surveillance systems during a natural disaster is relatively new and unusual. 29 The main lessons learnt are presented in Box 1.…”
Section: Discussionmentioning
confidence: 99%
“…Mobile phone-based syndromic surveillance system (Department of Health): piloted replacement of the existing paper-based system, with the findings that it was 'more timely (2.4 vs. 84 days), complete (70% vs. 40%), and sensitive (95% vs. 26%) than existing systems'. 60 The assessment found that the technology was simple to use, but that sub-national ownership was weak. The system is now being scaled up, to be established in at least one site per province.…”
Section: Figure 14 Main Reason For Washing Hands (Self-reported)mentioning
confidence: 99%